A Comparative Field Evaluation of the Effect of Growth Performance Between Porcine Circovirus Type 2a (PCV2a)- and PCV2b-Based Bivalent Vaccines Containing PCV2 and Mycoplasma hyopneumoniae - Cho, Hyejean; Oh, Taehwan; Suh, Jeongmin; Chae, Chanhee (Frontiers in Veterinary Science, 2022)
The objective of this study was to compare two different bivalent vaccines containing porcine circovirus type 2 (PCV2) and Mycoplasma hyopneumoniae. One vaccine contained PCV2a and the other contained PCV2b, and both were administered in a farm suffering from subclinical PCV2d infection and enzootic pneumonia. A total of 180 pigs were randomly divided into 3 groups (60 pigs per group; male = 30 and female = 30). Bivalent vaccination significantly improved growth performance in both vaccinated groups compared to the unvaccinated group. Growth performance as measured by body weight and average daily weight gain were not significantly different between the two bivalent-vaccinated groups. Both bivalent vaccines elicited high levels of neutralizing antibodies and interferon-γ secreting cells (IFN-γ-SC) against PCV2d, leading to a reduction in the levels of PCV2d blood viral load compared to unvaccinated animals. Similarly, both bivalent vaccines elicited high levels of IFN-γ-SC against M. hyopneumoniae that reduced the level of M. hyopneumoniae laryngeal viral loads compared to unvaccinated animals. Significant differences in severity of lung and lymphoid lesions were observed in both vaccinated groups compared to unvaccinated group. These comparative field data demonstrated that both bivalent vaccines are good candidates in controlling subclinical PCV2d infection and enzootic pneumonia in swine farms suffering from an existing infection.